INTERVENÇÃO DA ATENÇÃO PRIMÁRIA NA HIPERTENSÃO - Feitosa da Silva, Allynne Macêdo; Tolstenko Nogueira, Luciana; Tavares Castelo, Layse Caroline; Viana da Silva, Fátima Lidiane; Rodrigues Costa, Aylana Patricia; Luã Rabelo Chagas, Iago; Soares de Sousa, Mariane (SANARE - Revista de Políticas Públicas, 2015)
-